Exploring Human Capital And Work Ethics As Predictors Of OCB-O, OCB-I, And Performance In Life Insurance - Rosaman Taponao; Suhardi; Inda Sukati; Mauli Siagian (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
The life insurance industry is a knowledge-intensive and service-oriented sector in which organizational performance depends heavily on employee competence, ethical conduct, and discretionary work behavior. This study explores the role of Human Capital Management (HCM) and Work Ethics (WE) in predicting Organizational Citizenship Behavior directed toward the organization (OCB-O) and toward individuals (OCB-I), as well as their subsequent impact on employee performance. Drawing on the Resource-Based View, the study positions OCB as a behavioral mechanism through which human capital and ethical values are transformed into sustainable performance outcomes. This research adopts a quantitative approach using survey data collected from 250 employees working in life insurance companies in the Riau Islands Province, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Reliability, convergent validity, and discriminant validity were rigorously assessed, and common method bias was examined using procedural and statistical techniques. The results indicate that both HCM and WE have significant positive effects on OCB-O and OCB-I. Work Ethics emerged as a stronger predictor of citizenship behaviors compared to HCM, highlighting the importance of integrity, responsibility, and discipline in fostering extra-role behavior. Furthermore, both dimensions of OCB significantly enhance employee performance, with OCB-I exerting a stronger influence than OCB-O. Mediation analysis confirms that OCB-O and OCB-I partially mediate the relationships between HCM, WE, and performance, with OCB-I functioning as the most influential behavioral pathway. This study contributes to the literature by distinguishing between organizational and interpersonal dimensions of OCB and demonstrating their differential roles in the life insurance industry. Practically, the findings emphasize the need for organizations to integrate strategic human capital practices with strong ethical values to foster citizenship behaviors that drive superior performance. Future research is encouraged to adopt longitudinal designs and explore moderating variables such as leadership style and organizational culture.